The big shrink - Mlynowski, Sarah; Myracle, Lauren, 1969-; Jenkins, Emily, 1967- (Mlynowski, Sarah. Upside-down magic, 2019)
Marigold Ramos thinks that her magical ability to make things small will come in handy as she and her friends protest the new rule banning their toy dragons from school, until her magic gets out of control and starts shrinking her friends.